Impacts of Ultrasonic Energy on Washability, Sewability and Colour Properties of Materials in Enzymatic Process - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2011)
The short fibers on the cellulosic materials are removed by bio-processing and thus smoothing the surface. Within the scope of this study, materials on which cellulase enzyme was applied were washed through the ultrasonic probe method following bio-processing. Comparisons in terms of weight loss, whiteness levels and colour measures and changes of fabrics used in the study were carried out. Washing, rubbing, perspiration and Light fastness, pilling and stitching resistance and slipping properties of materials were also observed.
Keywords: Enzymes; Cellulose; Bio-seouring; Antipilling; Ultrasound; Colour differences; COTTON